2020
DOI: 10.1155/2020/2469436
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Gain Behavior and Prediction of Cement-Stabilized Macadam at Low Temperature Curing

Abstract: For cement-based materials, the curing temperature determines the strength gain rate and the value of compressive strength. In this paper, the 5% cement-stabilized macadam mixture is used. Three indoor controlled temperature curing and one outdoor natural curing scenarios are designed and implemented to study the strength development scenario law of compressive strength, and they are standard temperature curing (20°C), constant low temperature curing (10°C), day interaction temperature curing (varying from 6°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Kim et al [28] investigated the UCS development under curing temperatures of 5 • C, 20 • C, and 40 • C. The findings suggested slight differences during the initial process, while appearing nearly indistinctive with time. Xu et al [29] simulated local air temperature fluctuations and found that the UCS of 5% CSCS increases with prolonged curing time, with the rate of gain being lower at low temperatures compared to standard temperatures. Marzouk et al [30] conducted experiments over three months at five temperatures ranging from −10 • C to 20 • C, revealing a proportional relationship between UCS and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [28] investigated the UCS development under curing temperatures of 5 • C, 20 • C, and 40 • C. The findings suggested slight differences during the initial process, while appearing nearly indistinctive with time. Xu et al [29] simulated local air temperature fluctuations and found that the UCS of 5% CSCS increases with prolonged curing time, with the rate of gain being lower at low temperatures compared to standard temperatures. Marzouk et al [30] conducted experiments over three months at five temperatures ranging from −10 • C to 20 • C, revealing a proportional relationship between UCS and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…During the rainy season, the relatively high water can establish premature cracks in road pavement structures, allowing liquids to access and penetrate capillary and air voids, decreasing the durability of cement-based materials and AAMs [16][17][18]. Stabilizing materials with high moisture sensitivity decrease stiffness caused by excess moisture from an external environment [19,20], negatively impacting crucial pavement properties [21,22]. This problem results in redundant maintenance costs and cannot be resolved in many countries.…”
Section: Introductionmentioning
confidence: 99%